Differential fruitset between grapevine cultivars is related to differences in pollen viability and amine concentration in flowers. (12th November 2015) - Baby, T.; Gilliham, M.; Tyerman, S.D.; Collins, C.
Abstract: Background and Aims: Reproductive capacity among grapevine cultivars varies considerably and impacts yield. Bioactive amines are reported to be involved in many aspects of plant reproductive physiology. We aimed to examine the association between the reproductive performance of cultivars and the concentration of amines in the reproductive organs. Methods and Results: The reproductive performance of Shiraz, Merlot and Cabernet Sauvignon was assessed by determining fruitset, coulure index, millerandage index, pollen tube growth and stigma receptivity. Endogenous concentration of amines in flowers and berries was measured. Poor reproductive performance exhibited by Cabernet Sauvignon and Merlot compared with that of Shiraz was correlated with poor pollen viability. Amine profiles in the flowers and berries varied significantly among cultivars. A significantly higher concentration of diaminopropane was found in Merlot and Cabernet Sauvignon and correlated with a higher proportion of underdeveloped berries. An aromatic amine phenylethylamine was found to be the major free amine in the flowers of Merlot, a cultivar susceptible to poor fruitset. Conclusion: Variable reproductive performance exhibited by grapevine cultivars is related to differences in pollen viability and amine concentration in the reproductive organs. Significance of the Study: A better understanding of the association between reproductive performance and amines in the reproductive organs of grapevines has been achieved.